Kadar Tanin, Berat telur, Indeks Telur, dan Berat Kerabang Telur Itik yang Disamak Ektrak Etanol Kulit Manggis (Garcia Mangostana L ): Tannin Content, Egg Weight, Egg Index, and Weight of Tanned Duck Egg Centipede Mangosteen Skin Ethanol Extract (Garcia Mangostana L ) - Wicaksono, Putra Bangun; Rinawidiastuti, Rinawidiastuti (Jurnal Riset Agribisnis dan Peternakan, 2022)
Duck eggs have advantages when compared to purebred chicken eggs, namely high centipede thickness, greater egg weight, stronger yolk color and has a bluish skin color.  But the disadvantage of duck eggs is that they are more expensive. The purpose of this study was to determine the tanning effect of mangosteen peel ethanol extract on egg weight, egg index, and duck egg centipede weight.  The treatment in this study was ethanol extract levels, namely 0%, 10%, 20% and 30%. The 2nd treatment long store at room temperature for 6 weeks.  The results of the study were the tannin content of mangosteen peel powder of 0.6758, while the tannin content of mangosteen peel ethanol extract was 1.7442. Egg weight ranges from 68.22-70.25g, egg index of 79.46-82.32 and Weight of centipede of 8.84-8.71g. Ethanol extract levels had no effect on egg weight, egg index, centipede weight, and Haugh value.  But the length of storage has an effect on the weight of the egg, the weight of the centipede and the value of Haugh. The suggestion is that it is necessary to increase the concentration of ethanol extract levels to tan duck eggs.